Evaluation of N95 respirators on fit rate, real-time leakage, and usability among Chinese healthcare workers: study protocol of a randomized crossover trial - Lam, Simon Ching; Odetayo, Aderonke; Yu, Ignatius Tak Sun; So, Sony Nai Yeung; Cheung, Kin; Lee, Paul Hong; Suen, Lorna Kwai Ping (Frontiers in Public Health, 2023)
Background: N95 respirators are used to limit the transmission of respiratory viruses in clinical settings. There are two to three major types of N95 for all healthcare workers in Hong Kong. However, after the coronavirus outbreak and the consequent shortage of many commonly used respirators, several new N95 respirators were adopted temporarily in clinical settings without evaluation. Prior literature indicates that traditional N95 respirators used in hospitals in Hong Kong are not fit for Chinese people and have fit rates ranging from 50% to 60%. This study aims to investigate and compare the fit rate, real-time leakage, and mask usability of traditional and new N95 respirators among Chinese healthcare workers. Methods: This study will employ two sequential phases. Phase 1 has a cross-sectional exploratory design used to investigate the fit rate and mask usability of three types of respirators. Phase 2 will examine the effectiveness of respiratory protection by comparing traditional and new N95 respirators by a randomized crossover trial. Eligible participants will be randomly allocated through a controlled crossover experiment to either a traditional or new respirator group (n = 100 in each arm) during standard cardiopulmonary resuscitation (CPR). The primary outcome (real-time leakage) will be recorded at 30sec intervals during nasopharyngeal suctioning and cardiopulmonary resuscitation. The secondary outcomes are the fit rate and mask usability. After a 2min suctioning (15secs twice) and 4min one-person CPR, the fit rate (assessed by standard N95 fit testing) and mask usability (measured by self-reported mask usability scale) will be recorded as data of post-procedure. After 10mins rest, measurement of real-time leakage (i.e., crossover), fit test, and usability will be repeated. Discussion: The result of real-time leakage will be a vital indicator of the respiratory protection of Chinese healthcare workers while performing prevalent clinical procedures, such as resuscitation. The fit rate and usability result will serve as an essential reference for consumable purchase policy in clinical settings. Trial registration: ISRCTN registry: ISRCTN40115047. Retrospectively registered on May 9, 2023. https://www.isrctn.com/ISRCTN40115047